Histopathological and histochemical studies of two cases of enzootic ethmoidal tumour in cattle - Inada, Tetsuo; Tokarnia, Carlos Hubinger (Pesquisa Agropecuaria Brasileira, 2014)
Two cases of enzootic ethmoidal tumour in cattle, seen in the State of Rio de Janeiro, were examined further as a complement to previous studies. Histopathological studies indicated that the adenocarcinomatous cells seen in these tumours were very similar to the secretory cells of Bowman's gland of the olfactory mucosa, which are serous and mucous secreting. Histochemically, they showed similar reactions, characteristic of mucopolisaccharides. Although the yellowish-brown pigment found in Bowman's gland was not seen in the neoplastic cells, it was thought that the enzootic ethmoidal tumours probably had their origin in the Bowmau’s glands of the olfactory mucosa.